Study of Cytokine Production in a Tisssue Culture of Human Macrophages Stimulated by Metal Ions - Z. Venclíková; J. Bártová; J. Běláček (Czech Dental Chamber, 2013)
Introduction: Macrophages, the cells of the innate immunity play the significant role in immune reactions. In the early stages of inflammatory processes they are the main source of pro-inflammatory cytokines. Cytokines are produced during the interaction of cells with antigen and play an important role in the activation and regulation of immune response. Aim and Method: Our study aimed at exploring their production in a cell line THP1 (monocyte-macrophage cell line of human origin), cultivated for five days with an addition of salts of titanium, mercury, chromium, cobalt, nickel and palladium, which are frequent components of dental alloys. In the case of corrosion in the oral cavity environment these alloys can evoke in some patients a hypersensitive response. Results and Conclusion: The ions under study were found to affect the cells of the THP1 line to different extents, giving rise to a lowered but also enhanced production of chemotactic factors, pro-inflammatory cytokines and also cytokines participating in the regulation of the immune response. The influence of their production after exposition to metals can then lead to the development of an undesirable response to dental alloys.